Solitary colon metastasis from renal cell carcinoma nine years after nephrectomy: A case report. (2016) - Vo, Elaine; Palacio, Carlos H.; Omino, Ronald; Link, Richard E.; Sada, Yvonne; Avo, Artinyan
Highlights: Colon is a potential site for solitary metastasis from renal cell carcinoma (RCC). Recurrent disease after curative nephrectomy usually occurs within three years. Metastatic RCC should be considered in RCC patients with bowel obstruction. Abstract: Introduction: Renal cell carcinoma (RCC) is the most common renal malignancy in adults. Metastatic disease is relatively common at presentation and frequently involves the lung, bone, brain, liver and adrenal glands. After curative resection, there is a 30–40% risk of recurrence, and a 10% risk of developing metastatic disease after 5 years. The gastrointestinal tract, particularly the colon, represents a very uncommon site of late metastatic disease. Presentation of Case: We present a case of a 67 year-old-male who underwent a left radical nephrectomy for RCC 9 years before presenting with a metastatic large bowel obstruction. He was later found to have a near-completely obstructing mass in the rectosigmoid colon and underwent a sigmoidectomy with anterior resection of the upper rectum. Histopathology confirmed metastatic RCC confined to the colonic wall with negative microscopic margins. Discussion: The tendency of RCC to metastasize to unusual sites such as the pancreas or thyroid gland has been widely reported. However, cases of colon metastasis from RCC are extremely rare. Despite the absence of randomized prospective data, widespread consensus supports the surgical treatment of solitary and oligometastatic disease in light of the poor patient outcomes in non-surgically treated disease (Milovic et al., 2013) [3]. Multiple groups have reported favorable outcomes for surgically resected solitary metastatic disease with long disease-free intervals and good performance status. Conclusion: The colon is a potential, though uncommon, site for solitary metastasis from RCC. The clinical presentation is frequently several years after initial curative resection. Oncologic resection with negative margins may result in long-term survival in patients with isolated metastatic disease.